Electronic Properties of a Novel Boron Polymorph: Ogee-Borophene - B. Sarikavak-Lisesivdin; S. B. Lisesivdin (Advances in Condensed Matter Physics)
In this computational study, a novel borophene polymorph, Ogee-Borophene, characterized by irregular decagon-shaped hollows was reported. The structure involves a deviation from hexagonal configurations found in all other known borophene polymorphs. The decagon-shaped hollow is highly related to the anisotropy of the structure, which results in three types of boron atoms with different electronic properties in the structure. In the study, the electronic structure and density of states of this novel structure were investigated with the help of density functional theory calculations. The electronic structure of Ogee-Borophene shows Dirac cone formations near the Fermi level. The discovery of a novel borophene polymorph, Ogee-Borophene, with irregular-shaped hollows represents a different point of view in the 2D materials field. The unique electronic properties of this material suggest that Ogee-Borophene has the potential to be used in a variety of applications, including transistors, and selective sensor applications without the need for additional doping.